Investigating the existence of a "palaeo-foreshore" zone at Molos beach (Kefalos bay, Paros, Greece). - Poulos, S.; Ghionis, G.; Petrakis, S. (Bulletin of the Geological Society of Greece, 2013)
The present study investigates the existence of a "palaeo-foreshore zone" at Molos beach in or after 1884 A.D., as defined in the Greek legislation (Law 2971/ 19.12.2001). To this end, existing geological and climatological information were gathered, detailed geomorphological mapping was carried out and surficial sediment samples were collected along a shore-normal transect extending from the backshore to the nearshore (subaqueous) zone. In addition, sedimentological /stratigraphical data were obtained from two trenches (1.5 m and 3 m deep) that were excavated on the landward side of the coastal dunes. Topographic maps, aerial photographs and satellite images are used to study the recent changes of the shoreline position. On the basis of the above, it is concluded that the current backshore zone has recently evolved from a shallow lagoonal, to a terrestrial environment. The submerged beach rock formations are at similar water depths (0.3-0.4 m) with those observed in other islands of the Cyclades complex (i.e. Rhenia, Naxos) whose formation has been radio-carbon dated at least 200 years BP, indicating that the 1884 A.D. shoreline was not landward, but approximately 15 m offshore relative to its present position